EVALUASI PEMELIHARAAN DAN PERAWATAN BANGUNAN GEDUNG K. H. HASJIM ASJ’ARIE, KAMPUS A, UNIVERSITAS NEGERI JAKARTA - Widianto, Fajar (Menara: Jurnal Teknik Sipil, 2022)
This study aims to explain the suitability between the implementation of maintain and maintain (repair) of the building K. H. Hasjim Asj'arie, Campus A, Jakarta State University in the field with Standar Operating Procedures (SOP) and Minister of Public Works Regulation Number: 24/PRT/M/2008. The research systematic used in this study is to use the Discrepancy Evaluation Model or the gap evaluation model developed by Provus. In this research, the data collection method used is by means of observation, interviews and documentation. The results showed that for the maintenance aspect, the percentage of conformity between the Regulation of the Minister of Public Works Number: 24/PRT/M/2008 and SOP (Standar Operating Procedure) was 78% for architectural components and 48% for mechanical and electrical components, field conditions according to the Minister of Public Works Regulation Number: 24/PRT/M/2008 of 35% for architectural components and 65% for mechanical and electrical components. As for the maintenance (repair) aspect, the percentage of conformity between the Regulation of the Minister of Public Works Number: 24/PRT/M/2008 and SOP (Standar Operating Procedure) is 42%, the percentage result of conformity between field conditions and the Regulation of the Minister of Public Works Number: 24/PRT/M/2008 at 75%.